2020
DOI: 10.1039/d0cp00704h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystal size on methanol to hydrocarbon conversion over single crystals of ZSM-5 studied by synchrotron infrared microspectroscopy

Abstract: The induction period for alkene formation from methanol in single crystals of HZSM-5 decreases with decreasing crystal size and increasing temperature and hydrocarbon pool species are formed almost instantaneously at higher temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Copper-oxo species in other zeolites, including dimers in MOR and copper-oxo clusters in BEA and FAU, are less active in overoxidation. Therefore, methoxy species are stable until high temperature and undergo other ways of transformation, such as C–C coupling to ethane and propane, or decomposition to carbon monoxide. …”
Section: Discussionmentioning
confidence: 99%
“…Copper-oxo species in other zeolites, including dimers in MOR and copper-oxo clusters in BEA and FAU, are less active in overoxidation. Therefore, methoxy species are stable until high temperature and undergo other ways of transformation, such as C–C coupling to ethane and propane, or decomposition to carbon monoxide. …”
Section: Discussionmentioning
confidence: 99%
“…There is a great need for improved time resolution for the in situ techniques that are available to us. Inroads into this have been made with for example with the use of synchrotron infrared microspectroscopy where time resolution of 0.25s has been achieved 41,43 but we can expect further advances in this area. For example,it can be expected for oxidation reactions that epr spectroscopy can be expected to play enhanced role in the future since radical species are often involved in oxidations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they indicated the possibility of a CH 2 species being involved. Subsequently, 43 they studied the effects of crystal size on methanol to hydrocarbon conversion over single crystals of ZSM-5 using operando synchrotron infrared microspectroscopy. They studied methanol conversion with coffin-shaped HZSM-5 crystals of different sizes: large (∼250 × 80 × 85 μm 3 ), medium (∼160 × 60 × 60 μm 3 ) small (∼55 × 30 × 30 μm 3 ).…”
Section: Computer Modelling and Advanced Spectroscopy Studies Of The mentioning
confidence: 99%
“…Olefin oligomers (surface alkoxy groups) are the first adsorbed species containing carbon-carbon bonds to appear, and these subsequently cyclise to form methylcyclopentenyl cations as the first cyclic component of the HCP. In a subsequent paper 40 we showed that the induction period for the first direct formation of olefins shortened as the crystal size was decreased, and became negligible at higher temperatures, concluding that the HCP is formed almost immediately with small crystals at higher temperatures.…”
Section: Introductionmentioning
confidence: 87%